2017
DOI: 10.1093/tropej/fmx077
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Dengue Burden in Paediatric Patients in New Delhi

Abstract: Weather parameters seem to influence magnitude of dengue epidemic, particularly in dengue season. There is need to have an in-depth study about developing a prediction model for dengue epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This evidence is also supported by the results of a study conducted in Indonesia during the period of 2014 -2018 which shows that there is a correlation between relative humidity and DHF incidence, which is statistically significant (r = 0.413, p= 0.001) (Arsin et al, 2020). This is also supported by a Sri Lankan study, Bangladesh study, three Indonesian studies, Indian study and an Thailand study ; (Islam et al, 2021;Jat & Mala, 2017) (Roy et al, 2018) Tosepu et al, 2018(Ummi Khairunisa & Wahyuningsih, 2018;Salim & Syairaji, 2020;Tosepu, Tantrakarnapa, Worakhunpiset, & Nakhapakorn, 2018).…”
Section: Impact Of Humidity On Denguesupporting
confidence: 61%
See 1 more Smart Citation
“…This evidence is also supported by the results of a study conducted in Indonesia during the period of 2014 -2018 which shows that there is a correlation between relative humidity and DHF incidence, which is statistically significant (r = 0.413, p= 0.001) (Arsin et al, 2020). This is also supported by a Sri Lankan study, Bangladesh study, three Indonesian studies, Indian study and an Thailand study ; (Islam et al, 2021;Jat & Mala, 2017) (Roy et al, 2018) Tosepu et al, 2018(Ummi Khairunisa & Wahyuningsih, 2018;Salim & Syairaji, 2020;Tosepu, Tantrakarnapa, Worakhunpiset, & Nakhapakorn, 2018).…”
Section: Impact Of Humidity On Denguesupporting
confidence: 61%
“…Muurlink et al,2018 have revealed that the best predictors of an dengue outbreak are the number of rainy days in the preceding two months (Muurlink, Stephenson, Islam, & Taylor-Robinson, 2018). According to studies conducted in Indonesia and India, there is a significant association between cumulative rainfall (Ali et al, 2020;Arcari & Tapper, 2017;Arcari, Tapper, & Pfueller, 2007;Joshua, Kaliaperumal, Krishnamurthy, Muthusamy, Venkatachalam, Gowri, Shete, Ramasamy, Gupta, Murhekar, et al, 2020;Riyanto et al, 2020;Roy et al, 2018;Salamah et al, 2012). A significant weak correlation between higher rainfall and incidence of DHF cases has been found in two studies conducted in Indonesia (Haryanto, 2016); (Salim & Syairaji, 2020).…”
Section: Impact Of Rainfall On Denguementioning
confidence: 99%
“…Several outbreaks of DF have been reported over the past 2 decades 17 , 18 , 19 , 20 , 21 , 22 , 23 and a seasonal trend during the monsoon period has been noted 24 due to the warm environment and high relative humidity 25 favoring vector growth. The reported case fatality rate shows a declining trend 26 from 6–9% 17 , 18 , 27 to 0% 23 attributable to increased awareness and better case diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several studies have previously analyzed the clinico-epidemiologic profile of dengue infection. 11 , 12 , 13 In this study we evaluated patients with dengue presenting to the outpatient or emergency departments of a tertiary care hospital in an urban setting for their clinical and hematological profile, management and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This trend can be explained because of high relative humidity and warm environment which helps the growth of vector. 12 The varied clinical presentation of dengue has made clinical diagnosis difficult. Hence, the responsibility or burden of diagnosing dengue cases depends on standard and well equipped laboratory.…”
Section: Discussionmentioning
confidence: 99%